Penilaian Kinerja Bangunan Gedung Hijau Pada Tahap Perencanaan Teknis Melalui Aspek Efisiensi Penggunaan Energi di Rumah Inti Tumbuh Tahan Gempa (RITTA) Kota Prabumulih - Safrini, Yusra Dwi Yani; Aminuddin, Kiagus Muhammad; Usman, Arie Putra; Ramadhani, Ramadhani; Septriansyah, Verinazul (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2025)
A Green Building (BGH) is a building that prioritizes the efficient use of resources, is environmentally friendly, and takes into account its impact on human health. Assessing the performance of a Green Building is very important in efforts to achieve sustainable development. One of the main aspects of such an assessment is energy-use efficiency. This study aims to evaluate the energy efficiency performance of the Earthquake-Resistant Core Growing House (RITTA) in Prabumulih City at the technical planning stage. The research employs a research-based approach, with data collection through document studies, assessment instruments based on Green Building criteria, and appropriate data analysis methods. The results of the performance assessment of the Green Building in terms of energy-use efficiency at the technical planning stage show that the Earthquake-Resistant Core Growing House (RITTA) in Prabumulih City obtained an energy efficiency score of 67.39%. Based on the classification set out in the Ministry of Public Works and Housing Regulation No. 21 of 2021, this score places the building in the “Madya” (Intermediate) category. The recommendations from the performance assessment emphasize a combination of passive design strategies (such as ventilation and natural lighting), the selection of high-quality insulating materials, the utilization of renewable energy sources, and compliance with earthquake-resistant building standards. This approach will improve energy efficiency while maintaining the structural safety of the building against earthquake risks.